2013
DOI: 10.1089/tmj.2012.0132
|View full text |Cite
|
Sign up to set email alerts
|

Telemedicine Pre-anesthesia Evaluation: A Randomized Pilot Trial

Abstract: Telemedicine and in-person evaluations were equivalent, with high patient and provider satisfaction. Telemedicine provides potential patient time and cost saving benefits without more day of surgery delay in our system. A prospective trial of patients from multiple surgical specialty clinics is warranted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
87
0
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 84 publications
(93 citation statements)
references
References 23 publications
3
87
0
3
Order By: Relevance
“…3 The investigators reported equivalent patient and provider satisfaction as well as concordance with the physical exam when compared with the day of surgery. 3 We conducted a study investigating patient preferences regarding the use of telemedicine for the preoperative anesthesia assessment as well as patient opportunity costs to attend the preanesthesia clinic. The motivation for our study was based on the authors' observation that many preanesthesia clinic (PAC) patients were American Society of Anesthesiologists I or II physical status and oftentimes reported financial and time loss to attend the PAC.…”
Section: To the Editormentioning
confidence: 91%
See 2 more Smart Citations
“…3 The investigators reported equivalent patient and provider satisfaction as well as concordance with the physical exam when compared with the day of surgery. 3 We conducted a study investigating patient preferences regarding the use of telemedicine for the preoperative anesthesia assessment as well as patient opportunity costs to attend the preanesthesia clinic. The motivation for our study was based on the authors' observation that many preanesthesia clinic (PAC) patients were American Society of Anesthesiologists I or II physical status and oftentimes reported financial and time loss to attend the PAC.…”
Section: To the Editormentioning
confidence: 91%
“…Three recent pilot studies reported success in using dedicated telemedicine setups, including an electronic stethoscope and airway camera, for preanesthesia consultation by anesthesiologists. [1][2][3] The most recent study randomized 155 head and neck surgery patients to undergo either an in-person or a telemedicine preanesthesia evaluation. 3 The investigators reported equivalent patient and provider satisfaction as well as concordance with the physical exam when compared with the day of surgery.…”
Section: To the Editormentioning
confidence: 99%
See 1 more Smart Citation
“…Where suitable, telephone interviews can reduce the burden on preoperative assessment clinics, the number of "no shows", and the number of hospital trips and can potentially improve operation room utilization. 13,14 Using standardized health questionnaires has been shown to be a cost-effective approach, but this depends upon the patient's ability to assess his or her own health.…”
Section: Preoperative Assessmentmentioning
confidence: 99%
“…, Mulcaby & Pierce , Applegate et al . , Singh ). Successful preoperative nursing care requires strong organisational support; different guidelines and standardised procedures are needed (Bothe & Donoghue , Applegate et al .…”
Section: Introductionmentioning
confidence: 99%